Emerging technologies for studying DNA methylation for the molecular diagnosis of cancer. (June 2015) - Marzese, Diego M; Hoon, Dave SB
<x xml:space="preserve">Abstract</x> DNA methylation is an epigenetic mechanism that plays a key role in regulating gene expression and other functions. Although this modification is seen in different sequence contexts, the most frequently detected DNA methylation in mammals involves cytosine–guanine dinucleotides. Pathological alterations in DNA methylation patterns are described in a variety of human diseases, including cancer. Unlike genetic changes, DNA methylation is heavily influenced by subtle modifications in the cellular microenvironment. In all cancers, aberrant DNA methylation is involved in the alteration of a large number of oncological pathways with relevant theranostic utility. Several technologies for DNA methylation mapping have been developed recently and successfully applied in cancer studies. The scope of these technologies varies from assessing a single cytosine–guanine locus to genome-wide distribution of DNA methylation. Here, we review the strengths and weaknesses of these approaches in the context of clinical utility for the molecular diagnosis of human cancers.